DEMOGRAPHIC GEOGRAPHY OF KIDNEY TRANSPLANTATION IN CHILDREN IN RUSSIA - M. M. Kaabak; E. A. Molchanova; N. N. Babenko; A. K. Zokoev; S. V. Shchekaturov; Y. N. Vyunkova; Z. I. Kurakina (Union of pediatricians of Russia, 2013)
The article is dedicated to one of the most difficult issues of world pediatrics - kidney transplantation. It displays the register of transplantations in children conducted at 2 leading Moscow clinics in this sphere of medicine. The article presents the authors' experience of kidney transplantation, data on transplant survivability and discussion of the long-term results obtained in children from Moscow and other regions of the Russian Federation.